The Behavioral Incivility In Second-Year Nursing Students - Tahulending, Peggy; Manurung, Afse Windia; Purba, Elsa Pertiwi; Sibarani, Rifka Fiolisa (Jurnal Keperawatan Malang, 2024)
Background: Incivility behavior also occurs in the scope of education. The nursing education setting is also not free from the problem of incivility. The incidence of incivility or incivility behavior in nursing education is increasing so that it can affect the learning environment, the learning process in the classroom, and also during clinical practice. Pupose: The purpose of this study was to determine the description of Incivility behavior in second year nursing faculty students at University X Methods: The method in this study was descriptive quantitative with a cross-sectional approach. The population was 191 second-year nursing students. The Indonesian version of the Clark Civility Index for Students and Classmates questionnaire was used in this study. Univarite analysis was conducted in this study. The research time period with research time from January-April 2023. Results: The results showed that the level of Incivility behavior in second year nursing students was in the low category as many as 83 (43.5%) in the civil category and very incivility was only 0.5%. Likewise, the 61 (31.9%) classmates' assessment category is included in the civil category. Implication: The majority of respondents described behavior in the range of moderately civil to very civil. So it can be concluded that the level of Incivility behavior in second year students at one of the X Universities is in the low category. Keywords: Incivility,Nursing,Students